Analisis Faktor-Faktor yang Mempengaruhi Kesulitan Belajar pada Saat Pandemi Covid-19 : Penelitian pada Remaja Usia SMP dan SMA di Wilayah Makassar Jakarta Timur - Hamzah Robbani; Nuke Yuliana (Neolectura, 2022)
The purpose of the study was to determine the factors that influence learning difficulties during the Covid-19 pandemic in junior high and high school age adolescents in the Makassar area of ??East Jakarta. The research method used in this study is a qualitative method by analyzing the data from observations and interviews. The analytical technique used in this research is qualitative data analysis. The object of this research is junior high school and high school youth in Makassar, East Jakarta, with a total of 10 informants including 2 junior high school students and 8 high school students. Based on the research conducted, it is identified the factors that influence learning difficulties in the pandemic era in junior high and high school age adolescents in the Makassar area of ??East Jakarta including the difficulty of understanding material through distance learning, low interest in learning, difficult social adjustment, poor health. not good, lack of learning facilities, limited study space, materials.